Effect of Dietary Copra Meal on Growth Performance and Survival Rate of Red Tilapia (𝙊𝙧𝙚𝙤𝙘𝙝𝙧𝙤𝙢𝙞𝙨 𝙣𝙞𝙡𝙤𝙩𝙞𝙘𝙪𝙨 𝙭 𝙢𝙤𝙨𝙨𝙖𝙢𝙗𝙞𝙘𝙪𝙨) - Phumee, Preeda; Wattanabancha , Nattida (Burapha Science Journal, 2026)
The feeding trial was conducted to determine growth performance, survival rate and feed cost of red tilapia (Oreochromis niloticus – mossambicus). Four iso-nitrogenous (35% crude protein) and iso-lipidic (12% crude lipid) experimental diets containing 0, 3, 6, and 9 % of copra meal (CM0, CM3, CM6, CM9) were used. One hundred and twenty fish, with an initial weight of 14.28 ± 0.13 g were reared in twelve 500 - litre fiberglass tanks (10 fish /tank). Fish were fed twice a day (8 AM and 5 PM) for eight weeks. Growth performance, in terms of mean body weight, percentage weight gain (%WG), and specific growth rate (SGR) were found the best (p<0.05) in fish fed on diet containing 9 % of copra meal. Protein efficiency ratio (PER) of fish fed on control diet (CM0) was the highest (p<0.05).Feed conversion ratio (FCR) was found the lowest in fish fed on control diet, But was not significant different (p>0.05) to fish fed on diet containing 9 % of copra meal. . Feed cost showed the lowest in fish fed on diet containing 9 % of copra meal. The incorporation of copra meal can be reduced feed cost 2.44 Bath per kilogram equivalent to 10.23 %. The results indicated that copra meal can be incorporated into diet for red tilapia up to 9 % without any deleterious effect on growth performance, feed utilization and survival rate. Moreover, feed cost can be minimized.